Extension management and its role in facing the challenges of using solar energy systems in the agricultural sector from the point of view of agricultural employees in Salah al-Din Governorate / Iraq - Abdullah, Ahmed Saker; Adbullah, Rasha Raad; Salih, Khalaf Jasim; Shada, Maha Saeed; Farhan, Israa Sami (Edelweiss Applied Science and Technology, 2025)
The research objective is to ascertain the role of extension management in addressing the obstacles associated with implementing solar energy systems in the agricultural sector from the perspective of agricultural employees in Salah al-Din Governorate. Additionally, it aims to find the significant differences in determining the role of extension management according to some personal variables and to identify the role of extension management in the following domains: extension planning, institutional coordination and cooperation, extension training and qualification, financing and financial support, raising awareness and extension media, evaluating extension programs, extension human resources management, and developing extension policies. Agricultural employees employed by the Salah al-Din Agriculture Directorate and its affiliated agricultural divisions, as well as the extension center in Salah al-Din Governorate, comprised the research community, where the number of employees reached 407. A random sample of 35% was selected, resulting in 142 employees who underwent the research procedures. The questionnaire was prepared in two main parts. The first part includes a set of variables related to the personal aspect, and the second part consists of 40 paragraphs distributed over eight main domains that are answered through a three-point scale (High role, Medium role, Weak role). The results showed that the role of extension management, in general, was medium, tending toward weak. We conclude from this that there is a deficiency in providing the required technical and extension support and weak awareness of the importance and benefits of solar energy systems, which requires strengthening extension programs and developing more effective strategies to address these challenges. The results also showed significant differences between determining the role of extension management and each of the following variables: educational level, job experience, participation in extension activities, academic specialization, interest in modern technologies, and job satisfaction. The researchers recommended organizing regular seminars and training courses for agricultural employees to enhance their understanding of solar energy technology and modern agricultural extension management tools.